Synthesis and Evaluation of Multi Layered Magnetic Nanoparticles as Versatile Carrier for Anti-Cancer Drug Delivery: Pharmaceutical Science-Pharmaceutics for effective drug dosage - Subbiah Latha; Palanisamy Selvamani; Thangavelu Prabha; Jawahar Natarajan (International Journal of Life Science and Pharma Research, 2022)
The objective of this study is to develop a passive targeting of multilayered nanoparticles encountering multiple obstacles on the way to their target due to the mucosal barrier, nonspecific uptake of the drug. To prevent the nonspecific drug toxicity and combination chemotherapy for synergistic effect, multifunctional ferromagnetic properties were successfully fabricated by the layer-by-layer assembly (LBL) technique. The drug-loaded magnetic chitosan nanospheres were coated alternatively with sodium alginate and chitosan up to 3 layers incorporated with melphalan and methotrexate. The core-shell type composites consisting of magnetic nanoparticles decorated with biological substances are interesting for various biomedical applications. The magnetic property investigation reveals that drug-loaded nanomaterials exhibit superparamagnetic behavior. The uniformly distributed magnetic nanoparticles were also observed in scanning electron microscopic images to characterize the synthesized product. The thin film consisting of chitosan nanospheres was coated alternatively with sodium alginate and magnetic nanoparticles had a conductivity of two formulations F1a and F2a were 35.2 emu/g and 43.4 emu/g respectively. The formulation was evaluated for its particle size, size distribution, zeta potential, and in-vitro drug release in the pH of 1.2 and 7.0 fitted in kinetic release studies. The developed magnetic nanoparticles showed promising results with better- delayed drug action and will be an enhanced therapeutic means in combating the infections of cancer therapy.